The impact of impurities in various crude A. annua extracts on the analysis of artemisinin by liquid chromatographic methods - Pilkington, J.L.; Preston, C.; Gomes, R.L. (Elsevier, 2012)
Analysis of Artemisia annua extracts by liquid chromatographic methods has traditionally been complicated by the presence of significant quantities of impurities. It has been observed that these impurities often remain as a solid residue after sample reconstitution, but the possibility of artemisinin remaining entrained within this waxy layer has not been detailed in the literature. This investigation found that A. annua extract impurities have a critical impact on the quantification of artemisinin by liquid chromatographic methods. Extended sample reconstitution times of up to 24 hours are required in order for the mobile phase (acetonitrile) to penetrate the residue and solubilise the artemisinin contained within.